THE ARTISTIC AND MEANINGFUL ORIGINALITY OF THE STORY "THE WEAK HEART" BY F. M. DOSTOEVSKY - Chjen Elena Vitalyevna; Nazarova Shakhnoza (American Journals, 2022)
The story "Weak Heart" continues and develops one of the main essential themes of Dostoevsky's early work — the fate of a Dreamer in society. Due to the limited plot space, a small number of characters and the expression of the event series, the story tends to the dramatic kind of art.
Keywords: novel, dreamer